Oxidative Stress Biomarkers in the Equine Plasma and Erythrocytes Treated In Vitro by Leaf Extract Obtained From Ficus religiosa L. (Moraceae) - Tkachenko, Halina; Buyun, Lyudmyla; Osadowski, Zbigniew; Honcharenko, Vitaliy; Prokopiv, Andriy (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
In the present study, we highlight the antioxidant potential of aqueous extract of Ficus religiosa L. leaves in equine plasma and erythrocyte suspension. In this study, we have focused on the antioxidant effect of leaf extract obtained from F. religiosa on oxidative stress biomarkers [2-thiobarbituric acid reactive substances (TBARS), carbonyl derivatives content of protein oxidative modification (OMP), total antioxidant capacity (TAC)] using the equine erythrocytes model. Freshly collected leaves were washed, weighted, crushed, and homogenized in 0.1M phosphate buffer (pH 7.4) (in proportion 1:19, w/w). The equine erythrocyte aliquots and plasma were used in the study. A volume of 0.1 ml of the F. religiosa extract was added to 1.9 ml of clean equine erythrocytes or 1.9 ml of plasma. For positive control (blank), phosphate buffer was used. Treatment by extract reduced the erythrocytes TBARS level by 25.3 % (p=0.009), while plasma TBARS level was increased by 75.6 % (p=0.000), as compared to untreated erythrocytes. When plasma was incubated with extract, the ketonic derivatives level was significantly increased by 22.8 % (p=0.000), while non-significantly decrease both aldehydic and ketonic derivatives of OMP was observed. Treatment by F. religiosa extract caused the increase of TAC in plasma and erythrocyte suspension when compared to untreated erythrocytes. However, these changes were statistically non-significant. All these data suggest that F. religiosa could be explored for its antioxidant potential in equine erythrocyte suspension.